Does “Moringa Miracle” Happen to You Ever? - Sattar, Tabinda (Current Nutrition & Food Science, 2024)
This is a short discussion about an opinion on the limitless benefits of a miraculous tree, scientifically called ‘Moringa oleifera’. This article aimed to collect all the latest informational research about the tree whose every part is full of nutrients. This paper highlights all the possible ingredients present in moringa, its uses for every part of the human body, and its usefulness against certain important diseases. Intake of moringa, its benefits, and the prevention of some major diseases after using it, have been precisely discussed in this piece of research.
Keywords: better health